2006
DOI: 10.1016/j.cmet.2006.04.015
|View full text |Cite
|
Sign up to set email alerts
|

The circadian PAR-domain basic leucine zipper transcription factors DBP, TEF, and HLF modulate basal and inducible xenobiotic detoxification

Abstract: The PAR-domain basic leucine zipper (PAR bZip) transcription factors DBP, TEF, and HLF accumulate in a highly circadian manner in several peripheral tissues, including liver and kidney. Mice devoid of all three of these proteins are born at expected Mendelian ratios, but are epilepsy prone, age at an accelerated rate, and die prematurely. In the hope of identifying PAR bZip target genes whose altered expression might contribute to the high morbidity and mortality of PAR bZip triple knockout mice, we compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
434
2
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 461 publications
(457 citation statements)
references
References 45 publications
13
434
2
2
Order By: Relevance
“…The figure shows a representative experiment with four probes that cover a region from À197 to À113 and includes the only sequence that binds TEF as determined by using anti-FLAG antibodies sion of many enzymes and regulators involved in detoxification and drug metabolism. 5 However, the relevance of PAR bZIP proteins at the cellular level has not been thoroughly investigated. By using mouse tail fibroblasts from PAR bZIP (À/À) mice, we showed that PAR bZIP proteins, mainly TEF, were needed to maintain the basal mRNA levels of bik, a BH3-only proapoptotic member of the Bcl-2 family.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The figure shows a representative experiment with four probes that cover a region from À197 to À113 and includes the only sequence that binds TEF as determined by using anti-FLAG antibodies sion of many enzymes and regulators involved in detoxification and drug metabolism. 5 However, the relevance of PAR bZIP proteins at the cellular level has not been thoroughly investigated. By using mouse tail fibroblasts from PAR bZIP (À/À) mice, we showed that PAR bZIP proteins, mainly TEF, were needed to maintain the basal mRNA levels of bik, a BH3-only proapoptotic member of the Bcl-2 family.…”
Section: Discussionmentioning
confidence: 99%
“…4 These proteins have recently been shown to control the expression of many enzymes and regulators involved in detoxification and drug metabolism, such as cytochrome P450 enzymes, carboxylesterases, and constitutive androstane receptor. 5 In addition, we showed for the first time that PAR bZIP proteins regulate the expression of a gene, bcl-gS, involved in the execution of apoptosis. This transcriptional pathway can be activated by chemotherapeutic agents in cancer cells, thus contributing to the apoptotic response to chemotherapy.…”
mentioning
confidence: 99%
“…In their study, Stratmann et al (2010) have identified a special function of a BMAL1 binding site in the promoter region of the Dbp gene to adjust the phase of its expression according to the photoperiod. Since DBP and the related factors TEF and HLF regulate a variety of metabolic and detoxification enzymes prior to the food uptake of the animals (Gachon et al, 2006), this may be the rationale for this sophisticated regulation. The uncoupling mechanism provides flexibility to the phase of Dbp expression to ascertain that the DBP protein can activate the transcription of the metabolic and detoxification enzymes always prior to the food uptake of the organism.…”
Section: Transcriptional Network Of the Hepatic Circadian Oscillatormentioning
confidence: 99%
“…Interestingly, some factors involved in detoxification share both kinds of regulation. The xenobiotic compound sensor constitutive androstane receptor (CAR; NR1I3) is expressed in a circadian fashion in the liver (Gachon et al, 2006). However, in the presence of xenobiotic ligands, its expression is super-induced.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, hepatic lipogenesis, gluconeogenesis, heme, and bile acid biosynthesis as well as xenobiotic detoxification are cyclic in rodents and humans. [10][11][12][13] In contrast, some key regulators in circadian clock have their own metabolic functions. For example, RORa, activator of Bmal1, can regulate lipid flux, lipogenesis, and lipid storage in skeletal muscle.…”
mentioning
confidence: 99%